1991
DOI: 10.1113/jphysiol.1991.sp018442
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mechanisms for the transduction of acidic stimuli in rabbit carotid body glomus cells.

Abstract: SUMMARY1. The release of [3H]dopamine (DA) in response to inhibition of the Na+ pump or to intracellular acid load was studied in rabbit carotid bodies (CB) previously incubated with the precursor [3H]tyrosine. The ionic requirements of the release response and the involvement of specific ion transport systems were investigated.2. Inhibition of the Na+ pump, by incubating the CB with ouabain or in K+-free medium, evokes a DA release response which requires the presence of Na+ and Ca2+ in the medium and is ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
4
9

Year Published

1998
1998
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 36 publications
3
45
4
9
Order By: Relevance
“…We propose that, as for acidic and hypoxic stimuli, this [Ca¥]é response is a fundamental part of the chemotransduction process serving as the signal which evokes neurosecretion. This is supported by the observations that both the [Ca¥]é response and DNP-evoked neurosecretion are inhibited by the removal of extracellular calcium (Rocher et al 1991). It is apparent that the uncoupler-induced rise in [Ca¥]é is dependent upon cell membrane depolarization (Fig.…”
Section: Discussion Effects Of Uncouplers On [Ca¥]é Regulationsupporting
confidence: 73%
See 3 more Smart Citations
“…We propose that, as for acidic and hypoxic stimuli, this [Ca¥]é response is a fundamental part of the chemotransduction process serving as the signal which evokes neurosecretion. This is supported by the observations that both the [Ca¥]é response and DNP-evoked neurosecretion are inhibited by the removal of extracellular calcium (Rocher et al 1991). It is apparent that the uncoupler-induced rise in [Ca¥]é is dependent upon cell membrane depolarization (Fig.…”
Section: Discussion Effects Of Uncouplers On [Ca¥]é Regulationsupporting
confidence: 73%
“…Figure 3A shows that replacing Naº with NMDG caused a substantial inhibition of the [Ca¥]é response to DNP (Ä[Ca¥]é (control vs. Na¤-free conditions): 447 ± 71 vs. 58 ± 14 nÒ, n = 4, P < 0·05). These data are consistent with the rise in [Ca¥]é being due to reverse mode Na¤-Ca¥ exchange (Rocher et al 1991). We have, however, previously reported that Na¤-free conditions inhibit the [Ca¥]é response to physiological acidic stimuli via an alternative mechanism.…”
Section: Cause Of Uncoupler-induced Rise In [Ca¥]ésupporting
confidence: 80%
See 2 more Smart Citations
“…Such findings have led to the suggestion that acidosis, like hypoxia, evokes secretion from type I cells via membrane depolarization and subsequent Ca¥ influx through voltage-gated Ca¥ channels. However, such a mechanism has not yet been directly demonstrated, and there is evidence in the rabbit type I cell that acidevoked transmitter release arises from accumulation of intracellular Na¤ (due to stimulation of Na¤-H¤ exchange) which is sufficient to reverse Na¤-Ca¥ exchange (Rocher et al 1991), thereby allowing Ca¥ entry via transporters rather than ion channels. Thus, it was of importance to investigate the mechanism underlying acid-evoked secretion in PC12 cells.…”
Section: Discussionmentioning
confidence: 99%